Is the Integrated Treatment of Languages a good option? Perceptions of Primary Education Teachers - Boillos Pereira, Mari Mar; Aranberri Monasterio, Nora; Zuloaga Román, Eneko; Ibarluzea Santiesteban, Miren (Didáctica. Lengua y Literatura, 2022)
The Integrated Treatment of Languages (ITL) has gained popularity in the last decade in communities with multilingual educational systems such as that of the Basque Country. The objective of this approach is to design curricula that involve all the agents responsible for the teaching and use of the languages in the school environment. The challenge here is to create didactic interventions that enable the transfer of knowledge between the languages and that improve the students’ communicative competence. Thirty six Primary Education teachers from the Basque Autonomous Community who were receiving training in TIL on a voluntary basis participated in this study, which aims to find out what the teachers think about the implementation of this methodological approach. Specifically, after participating in guided discussion forums, they were asked to create SWOT matrices about their perceptions of the implementation of the approach. The qualitative analysis of the matrices shows that, in general, teachers are concerned about their role, but do not so much question the benefits of applying the methodology for the students. The results of this study allow inferring lines of action for teacher training programmes in ITL and for management tools in educational centres.
Keywords: Primary Education; multilingualism; Integrated Treatment of Languages; attitudes